Qualidade do leite materno em banco de leite humano : aspectos bacteriológicos, físico-químicos e perfil de aminas bioativas. - Fabiane de Fatima Silva (2008)
The objective of this work was to evaluate the influence of collection and processing the practices used by Human Milk Centers (HMC) on the profile and levels of bioactive amines and physico-chemical and bacteriological quality of human milk. The usual practices werefollowed in a HMC located in the metropolitan region of Belo Horizonte, MG, Brazil. The human milk collection and processing practices followed the recommendations established by ANVISA. However, they were not enough to assure the quality of the milk, resulting in a high percentage of milk loss. The human milk had good sensory quality, predominanceof 4.0 to 5.0 ºD acidity and energetic content between 500 and 700 kcal/L. Among the ten amines investigated, nine were detected: spermine, spermidine, putrescine, cadaverine, phenylethylamine, histamine, tryptamine, tyramine and serotonin. Spermine was the prevalent amine, followed by spermidine. 90% of the pasteurized milk showed absence oftotal coliforms and had a similar profile of amines compared to the raw milk. In order to evaluate the influence of pasteurization at 62 ºC/30 min, the Mann-Whitney U statistical test was used and indicated significant difference only for histamine, which increased during pasteurization (p < 0.05).